Ash trees in Great Britain: How might land-managers respond to a new threat? - C. Hall; M. Marzano; B. Karlsdóttir; T. Clarke; A.J. Dyke; J. Morris; N. Brown; V. Alonso-Chávez; A.E. Milne; L. O’Brien (Trees, Forests and People, 2025)
Ash trees across Great Britain are under increasing threat from pests and diseases as ash dieback (ADB) continues to spread and intensify in impact. Meanwhile, concerns grow throughout Europe about the westward spread of emerald ash borer (EAB). Should EAB be discovered in Great Britain, decisions taken by managers of ash trees will be crucial to their survival, given the threat they already face from ADB. This study has investigated the likely responses of land-managers to EAB, their willingness to implement surveillance for EAB, their knowledge of EAB, and the importance of ash trees to them. An online questionnaire was conducted in 2021 with diverse land-managers across Great Britain. Analysis of 368 completed questionnaires revealed some of the potential influences on decisions that land-managers might make concerning surveillance and management for EAB. These include: the personal importance of ash trees to land-managers, their perceptions of EAB risk, previous experience with ADB, self-reported knowledge of EAB, and management aims for the trees. Overall, the results demonstrate a range of likely responses to EAB. Understanding likely responses will help policymakers better plan for the potential arrival of EAB by highlighting where and how interventions and support might be most effective. Findings have practical value for land-managers and decision-makers, policy relevance for governance, and also add to the evidence about land-manager decision-making when faced with dual environmental threats.